Vortex flow hypothesis for a yawed rotor blade in reverse flow*. (March 2015) - Mayo, Michael; Raghav, Vrishank; Komerath, Narayanan
Rotating blades at high advance ratios can experience reverse flow on the retreating side of the rotor disc, where the freestream flow is directed from the sharp trailing edge of the blade to the blunt leading edge. Better understanding of this flow regime can help advance the design of high-speed rotorcraft. In this work, it is hypothesized that the sharp trailing edge of a reverse flow blade develops an attached vortex in a similar manner to a sharp-edged delta wing. Lift, drag, and pitching moment data for a static yawed blade in reverse flow are acquired using a load cell and the lift measurements are compared to predictions made with an adaptation of the Polhamus model. Surface tuft flow visualization confirms the presence of an attached spanwise vortex on the blade. Surface flow behavior is used to explain the behavior of observed aerodynamic loads, and correlations are made to previous results found in the literature. Vorticity transport analysis is used to justify the surface flow behavior variation with yaw angle and angle of attack.